The role of government interventions in household climate adaptation on the Tibetan Plateau. (October 2022) - He, Xinjun; Yan, Jianzhong; Yang, Liang Emlyn; Zhou, Hong; Wu, Ya; Wu, Shihai
Abstract: As climate change and its impacts intensify, the role of governments in the climate adaptation process has received widespread attention. Effective adaptation to climate change depends not only on whether households or communities adopt appropriate adaptation strategies but also on whether governments intervene effectively. To improve the understanding of the role of government interventions in households' climate adaptation processes, we propose a climate adaptation framework that takes government interventions into consideration at the household level. Based on a household survey in the Pumqu River Basin on the Tibetan Plateau, we discuss the impacts of government interventions on households' climate change adaptation. The results show that government interventions have: 1) buffered the risks and shocks of climate change to households' livelihoods; 2) shaped households' cognitions of climate change; 3) mediated the impact of households' livelihoods and climate change cognitions on their adaptation strategies; and 4) directly influenced households' livelihoods and their choices of climate adaptation strategies. Our findings emphasize the interfaces between government interventions and household adaptation, which not only helps governments clarify some principles when planning climate interventions but also has important implications for them to better guide households to adapt to climate change. Highlights: A household climate adaptation framework that emphasizes the role of government interventions was proposed. How households adapt to climate change under government interventions was explored. Verified the role of government interventions based on household survey data on the Tibetan plateau. Results were conducive to government to improve their climate actions.